Busca pela padronização de um modelo animal de depressão para estudos do eixo microbiota-intestino-cérebro - Lima, Júlia Martins de (2022)
The set of intestinal microorganisms and their metabolic products are recognized by physiological regulatory activity in many processes in the human body, including the regulation of the Central Nervous System. Neuropsychiatric disorders such as depression, and their treatment, seems to be under great influence of these commensals. Although many studies demonstrate alterations in the intestinal microbiota of animal models of depression, there is still great variability among the findings. Many of the dissimilarities depend on factors such as the experimental design, the diet of the animals, the nature, time and intensity of the induction protocols, the collection of samples, the fecal DNA extraction method, as well as the sequencing and bioinformatics techniques used for microbiota analysis. In this context, the work aimed to standardize an animal model of depression for studies of the microbiota-gut-brain axis. The animals were exposed to a six-week Moderate Unpredictable Chronic Stress protocol and orally treated with Sertraline for three weeks (10 mg/Kg). At the end of the protocol, the animals underwent behavioral tests to assess locomotor, social, depressive and anxiolytic behaviour. Fecal samples were collected being processed for targeted sequencing of the 16S rRNA gene. The results showed that the proposed model was capable of causing phenotypic changes in the animals, but not behavioral changes. The model also did not prove to impact the diversity indices of the intestinal microbiota of the animals. Thus, it was concluded that the model was not satisfactory for studies of the microbiota-gut-brain axis. A continuous search for the standardization of animal models for the study of the microbiota-gut-brain axis is necessary, in order to improve the reproducibility of the works and guarantee more consistent and representative results.